Prevention of Violence against Women - Sharma, Savita; Deepti, Parashar (Journal of Social Science and Humanities, 2025)
Violence against women has long been a problem in times of peace and war. It causes pain and suffering for the victims and their families and puts a heavy burden on the international community. Violence against women is a social problem based on the agreement between the rights of men and women. Two types of violence against women are physical and sexual abuse by intimate partners. Often, it happens in close relationships. The aim of this article is to conduct a critical analysis of violence against women. This article shall keep its prime focus on gender, discrimination, and punishment. Violence has many connotations, including physical, economic, and psychological, including stalking and pestering. This being a universal issue, it inflicts a great impact on victims’ families and communities.